Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s41666-020-00090-4
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of COVID-19 Based on Short-Duration Acoustic Smartphone Speech Analysis

Abstract: Currently, there is an increasing global need for COVID-19 screening to help reduce the rate of infection and at-risk patient workload at hospitals. Smartphone-based screening for COVID-19 along with other respiratory illnesses offers excellent potential due to its rapid-rollout remote platform, user convenience, symptom tracking, comparatively low cost, and prompt result processing timeframe. In particular, speech-based analysis embedded in smartphone app technology can measure physiological effects relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
0
23
0
1
Order By: Relevance
“…Coppock et al [21] reported lower UAR and area under the receiver operating characteristic curve (AUC) scores when distinguishing COVID-19 positive speakers with a cough from COVID-19 negative speakers with a cough. Stasak et al [25] similarly obtained chancelevel results when regarding COVID-19 positive and negative speakers with moderate COVID-19-like symptoms. Conversely, Han et al [22] reported a high rate of asymptomatic patients getting misclassified as healthy speakers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Coppock et al [21] reported lower UAR and area under the receiver operating characteristic curve (AUC) scores when distinguishing COVID-19 positive speakers with a cough from COVID-19 negative speakers with a cough. Stasak et al [25] similarly obtained chancelevel results when regarding COVID-19 positive and negative speakers with moderate COVID-19-like symptoms. Conversely, Han et al [22] reported a high rate of asymptomatic patients getting misclassified as healthy speakers.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, well-founded and not surprisingly, there is also a growing body of research on the automated detection of COVID-19 from voice. Several research groups in the domain of computational paralinguistics have focused their efforts on collecting large 'crowdsourced' datasets (e. g., [17,18,19,20]) using them to create machine learning models (e. g., [21,22,23,24,25,26]). Since voice is a readily available modality and the collection of voice data is non-invasive, voice-based models for COVID-19 detection could serve as valuable screening instruments [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ref. [ 25 ] performs COVID-19 diagnosis using short-duration acoustic smartphone speech analysis. Moreover, authors in [ 26 ] provide a design study of an AI-enabled framework to diagnose COVID-19 using a smartphone.…”
Section: Literature Review Background and Motivationmentioning
confidence: 99%
“…Existing literature has mainly investigated the information content of different audio modalities (e.g. cough, breathing, and voice) [7,8,9,10,11] and the power of various machine learning techniques, especially deep neural networks for COVID-19 detection [12,13,14,15,16,17,18,19]. While success has been witnessed recently in COVID-19 detection from audio signals through machine learning techniques [10], there is still a paucity of work on continuous monitoring of COVID-19 disease progression.…”
Section: Introductionmentioning
confidence: 99%